2022
DOI: 10.1094/pdis-04-21-0885-re
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Inheritance of Sclerotinia Stem Rot Resistance in Brassica napus and Relationship to Cotyledon and Leaf Resistances

Abstract: Sclerotinia sclerotiorum is a necrotrophic fungus causing devastating stem rot and associated yield losses of canola/rapeseed (Brassica napus) worldwide, including in Australia. Developing host resistance against Sclerotinia stem rot is critical if this disease in canola/rapeseed is to be successfully managed, as cultural or chemical control options provide only partial or sporadic control. Three B. napus breeding populations, C2, C5 and C6, including the parents, F1, F2, BC1P1 and BC2P2, were utilised in a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 64 publications
3
13
0
Order By: Relevance
“…Both additive and non-additive genetic effects influenced Sclerotinia stem rot resistance, as evidenced by significant mean squares of lines, testers, and line × tester interactions for both resistance evaluation criteria, namely, MLL and DSI. These findings are consistent with those of Khan et al [ 32 ], Disi et al [ 30 ], Godoy et al [ 59 ], Castano et al [ 60 ], and Achbani et al [ 61 ], who found that both additive and non-additive genetic action influenced Sclerotinia rot resistance inheritance and could be improved using the recurrent selection procedure. The significant effect of GCA on the sum of squares of SCA suggested that early generation selection of resistant progenies could be successful.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Both additive and non-additive genetic effects influenced Sclerotinia stem rot resistance, as evidenced by significant mean squares of lines, testers, and line × tester interactions for both resistance evaluation criteria, namely, MLL and DSI. These findings are consistent with those of Khan et al [ 32 ], Disi et al [ 30 ], Godoy et al [ 59 ], Castano et al [ 60 ], and Achbani et al [ 61 ], who found that both additive and non-additive genetic action influenced Sclerotinia rot resistance inheritance and could be improved using the recurrent selection procedure. The significant effect of GCA on the sum of squares of SCA suggested that early generation selection of resistant progenies could be successful.…”
Section: Discussionsupporting
confidence: 92%
“…The heritability of Sclerotinia stem rot resistance evaluation parameters (MLL and DSI) was moderate, indicating that early selection for Sclerotinia stem rot resistance may be successful. Sclerotinia stem rot resistance has been estimated to be heritable by various researchers, with values ranging from 21 to 88% [ 32 , 84 , 85 ]. Genetic advance as percent of mean (GAM) values are divided into three categories: low (0–10%), moderate (10–20%), and high (>20%) [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Information regarding the pattern of inheritance as well as the nature of gene action involved in resistance against Sclerotinia sclerotiorum helps crop geneticists and breeders to elect appropriate selection methods for breeding resistant cultivars. Previous studies have revealed that inheritance of Sclerotinia stem rot resistance varies from crop to crop being monogenic in Vicia faba [55] while polygenic in B. napus [23,32]. Our study is perhaps the first to report on the genetic investigation and protein expression patterns of Sclerotinia stem rot resistance in B. juncea.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, host genetic resistance is the most convenient, economic, and eco-friendly approach for the effective control of this devastating pathogen [18,19]. Earlier attempts to identify resistant sources against this disease in Indian mustard were hampered as all the B. juncea genotypes evaluated were found susceptible to Sclerotinia stem rot and any of the resistant sources reported belonged to other cruciferous crops and its wild relatives such as Brassica napus, B. fruticulosa, B. rupestris, B. incana, B. insularis, B. villosa, Erucastrum cardaminoides, E. abyssinicum, Sinapis alba, and Diplotaxis tenuisiliqua [20][21][22][23][24][25][26][27][28][29][30][31][32], with no reports available about its resistance in B. juncea, which is an important oil yielding crop in the Indian context. However, in recent few years, increasing attention has been paid which has ultimately led to the identification of a few Indian mustard genotypes resistant against this pathogen [3,5,33,34].…”
Section: Introductionmentioning
confidence: 99%